Depression and anxiety prevalence and correlations among cancer patients at Tikur Anbesa Hospital in Addis Ababa, Ethiopia, 2018: Cross-sectional study - Abraham, Yacob; G/Tsadik, Meseret; Gebeyehu, Abebaw; Fanta, Tolesa; Ashegu, Tebeje (Frontiers in Psychiatry, 2022)
Background: People with cancer, as well as their family members and loved ones, frequently experience distress. Distress can sometimes escalate from a normal level to one that interferes with therapy, makes it difficult for you to function or cope, and has an impact on many aspects life. Objectives: The objectives of this study was to assess the prevalence and correlates of depression and anxiety among cancer patients attending treatment at Tikur Anbessa specialized hospital. Methods: Hospital based cross-sectional study was conducted from April 15 to May 15, 2018. This study was conducted at Tikur Anbessa Specialized Hospital is in Addis Ababa, capital city of Ethiopia. The Hospital Anxiety and Depression Scale was used to collect an outcome variable (the presence of anxiety and depression). Result: According to the result of this study; being female sex, low educational status, current bleeding, younger age groups (30 to 39) years, and feeling pain had association before and after adjustment. With AOR of 2.18 (1.38-3.44), 1.73 (1.10-2.85), 2.57(1.61-4.11), 2.28(1.12-4.63), 1.64 (1.00-2.69) respectively showed significant association with prevalence of depression with 95% Cl. Whereas marital status with AOR 2.10(1.01-4.02), feeling discomfort 2.06(1.00-3.03), and bleeding 3.52(2.31-5.64) were found to be significantly linked with prevalence of anxiety. Accordingly anxiety and depression were present in 54.6 percent and 40.4 percent of the Tikur Anbessa Specialized Hospital's cancer patients, respectively. Factors that were strongly associated with depression were being a woman, having less education, bleeding right now, being younger (30 to 39 years old), and suffering discomfort. With AOR of 2.18 (1.38-3.44), 1.73 (1.10-2.85), 2.57(1.61-4.11), 2.28(1.12-4.63), 1.64 (1.00-2.69) respectively with 95% CI. On the other hand factors significantly associated with anxiety among cancer patients attending treatment at Tikur Anbessa specialized hospital were marital status with AOR 2.10(1.01-4.02), feeling discomfort 2.06(1.00-3.03), and bleeding 3.52(2.31-5.64. Conclusion: Guidelines for screening and treating depression and anxiety in cancer patients should be developed by psychiatry departments in collaboration with oncology department. Oncology and psychiatry department better work and capacitate link to help for good of patients. To enhance and widen the current findings, additional research on depression and anxiety risk factors should be done.